Democratic teachers: Do they exist in Indonesian high schools? - Abdullah, Umar; Hanan, Djayadi (Indonesian Research Journal in Education |IRJE|, 2025)
Democracy can thrive well in societies where individuals practice democratic values in their daily lives. Such democratic attitudes can be obtained through education that applies democratic principles. This study aims to explore how students in Indonesian high schools perceived the democratic attitudes exhibited by their teachers during instruction. Guided by a quantitative research design, the study involved 180 respondents conveniently chosen from 12 high schools in West Sumatra, South Kalimantan, DI Yogyakarta, and DKI Jakarta provinces. Data were elicited through a survey questionnaire and analyzed using descriptive statistics. The study findings indicated that participants viewed teachers in provinces with a high democracy index as demonstrating democratic attitudes on most survey items, in contrast to those in areas with a low democracy index. The participants noted that teachers' democratic attitudes in teaching enhance their motivation to study and elevate their academic achievement. This study underscores the necessity of fostering teachers’ democratic attitudes in teaching through teacher professional development programs.